THE IMPLEMENTATION OF POE2WE MODEL USING SCIENTIFIC APPROACH IN LINEAR LEARNING IN SENIOR HIGH SCHOOL - Nana Nana (Universitas Sebelas Maret, 2018)
Abstract: This research aimed to find out and to analyze the difference between the students receiving learning using the scientific approach with POE2WE model and those receiving PBL learning model, and to find out the model effectiveness of Physical learning in Senior High Schools. The sample of research was the students of Senior High Schools in Ciamis Regency taken randomly (using a random sampling technique). The research method employed was a comparative study conducted in several schools in Ciamis Regency becoming the model of the 2013 curriculum application in the school year of 2013/2014 in the Linear Movement Material of Tenth Grade. To collect the data, several research instruments were used: pre-test and post-test, student questionnaire, observation on the implementation of POE2WE model learning and interview to get the teachers’ response. The data were analyzed using the t-test to see the difference of normalized gain in two groups. The result of research showed that there was a significant difference the students receiving learning using a scientific approach with POE2WE model and those receiving PBL learning model. The data showed that the mean scores of pretest and posttest for the learning using POE2WE model and the one using the PBL model were 42.50 and 29.93, respectively and there was an increase in the mean class learning outcome with N-gain = 0.8 (high category) for POE2WE model and N-gain = 0.5 (medium category) for the PBL model. The effectiveness test obtained Sign value (2-tailed) (0.000) < α (0.05) meaning that POE2WE model was more effective than the PBL model.